2023
DOI: 10.14740/cr1523
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Glucagon-Like Peptide-1 Receptor Agonist on the Cardiovascular Outcomes in Patients With Type 2 Diabetes Mellitus: A Meta-Analysis and Systematic Review

Abstract: Background Since 2005, the cardioprotective effects of glucagon-like peptide 1 receptor agonists (GLP-1 RAs) have garnered attention. The cardioprotective effect could be an added benefit to the use of GLP-1 RA. This systematic review and meta-analysis aimed at summarizing observational studies that recruited type 2 diabetes individuals with fewer cardiovascular (CV) events before enrolling in the research. Methods Systematically, the databases were searched for observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A systematic review and meta-analysis aimed at summarizing the observational studies that recruited in-dividuals with type 2 diabetes that had had fewer CV events before enrolling in the research. The meta-analysis showed that GLP-1 RA therapy was associated with a significantly lower risk of MACEs, extended MACEs, all-cause mortality and CV mortality [148].…”
Section: The Vasculoprotective Effects Of Glp-1rasmentioning
confidence: 98%
“…A systematic review and meta-analysis aimed at summarizing the observational studies that recruited in-dividuals with type 2 diabetes that had had fewer CV events before enrolling in the research. The meta-analysis showed that GLP-1 RA therapy was associated with a significantly lower risk of MACEs, extended MACEs, all-cause mortality and CV mortality [148].…”
Section: The Vasculoprotective Effects Of Glp-1rasmentioning
confidence: 98%
“…In people with established cardiovascular disease or at high risk for cardiovascular disease, GLP-1 RA and SGLT2i have been recommended by the consensus reports of the ADA and the EASD since 2018 [36]. This recommendation was based upon established cardiovascular disease benefit as demonstrated in clinical trials and observational studies [13,14,[37][38][39]. That so few patients were subsequently prescribed GLP-1 RA following incident stroke in the present study (6.6%) likely reflects the lack of recommendations for the use of these treatments to prevent cardiovascular disease in most of the years covered by this study [6].…”
Section: Relation To Previous Studiesmentioning
confidence: 99%
“…This suggests the potential to enhance a patient's cardiac profile concurrently with diabetes treatment. 10 Presently accessible GLP-1R agonists, owing to their peptidic agonist structure, necessitate subcutaneous administration. Though compelling, this approach proves cumbersome for many patients, potentially leading to decreased adherence compared to those on oral medications.…”
Section: Introductionmentioning
confidence: 99%